Anomalous collective modes in atomic nuclei within the proton-neutron interacting boson model - Wei Teng; Yu Zhang; Sheng-Nan Wang; Feng Pan; Chong Qi; J.P. Draayer (Physics Letters B)
Novel collective modes characterized by a B4/2 ratio (≡B(E2;41+→21+)/B(E2;21+→01+)) less than 1.0 that were observed recently have been identified within the proton-neutron interacting boson model (IBM-2) using the consistent-Q Hamiltonian. These modes are shown to give rise to triaxial spectral features, including significant band mixing. The results provide a compelling explanation for the deeply suppressed B4/2 ratio observed in 166W, 168,170Os, and 172Pt, offering new insights into the B(E2) anomaly phenomenon in neutron-deficient nuclei.